1990
DOI: 10.1111/j.1439-0418.1990.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour and food preferences of the pest species comprising the Epilachna vigintioctopunctata (F.) complex (Col., Coccinellidae)

Abstract: Food acceptance trials involving 34 species belonging to five plant families confirm Epilachna cucurbitae Richards feeds exclusively on Cucurbitaceae and both E. 26‐punctata 26‐punctata (Boids.) and E. 28‐punctata pardalis (Boisd.) feed exclusively on Solanaceae. Leaves and fruit are preferred by the two solanivorous species. Flowers, especially pollen, are preferred by E. cucurbitae, with beetles acting as pollinating agents. This is the first record of such behaviour in a phytophagous coccinellid. Food prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Therefore, it was evident that the beetle mostly preferred Thamba followed by ISD 006 whereas Bijoy and BAU-2 were the least preferred hosts and remaining other brinjal varieties were moderately preferred by the beetle at three different temperature regimes. Richards and Filewood (1990) stated that host preference of E. vigintioctopunctata was influenced by odour, taste and age of plant and by thickness of leaves, proportion of crude fibers, parenchymatous tissue, and water content. They also stated that temperature has some effect on the host preference of this species of Epilachna beetle.…”
Section: Effect Of Temperature On Host Preferencementioning
confidence: 99%
“…Therefore, it was evident that the beetle mostly preferred Thamba followed by ISD 006 whereas Bijoy and BAU-2 were the least preferred hosts and remaining other brinjal varieties were moderately preferred by the beetle at three different temperature regimes. Richards and Filewood (1990) stated that host preference of E. vigintioctopunctata was influenced by odour, taste and age of plant and by thickness of leaves, proportion of crude fibers, parenchymatous tissue, and water content. They also stated that temperature has some effect on the host preference of this species of Epilachna beetle.…”
Section: Effect Of Temperature On Host Preferencementioning
confidence: 99%
“…The phytophagous ladybird beetle Epilachna vigintioctopunctata (Fabricius) is widespread in Asia and Australia, where it is notorious for causing severe damage to solanaceous crops such as eggplants and tomatoes (Dieke, 1947;Li and Cook, 1961;Pang and Mao, 1979;Hoang, 1983;Richards, 1983;Katakura et al, 1988;Richards and Filewood, 1990;Park and Yoon, 1991;Li, 1993;Shirai and Katakura, 1999). Furthermore, occurrence of this species on a leguminous weed Centrosema pubescens in Java and Sumatra was recently reported (Nishida et al, 1997;Shirai and Katakura, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, they can use photoreceptors, mechanoreceptors and/or chemoreceptors (e.g., Chapman 2003; Richards and Filewood 1990;Tol and Visser 2002) but specialised sensory hairs mediating olfactory and gustatory information seems to be the most important, particularly at close distance. Many studies have shown that host plants are recognised based on specific ratios of ubiquitous compounds (e.g., Bruce et al 2005) such as plant volatiles, which are detected by insect antennae (e.g., Chinta et al 1994;Schooley and Wiens 2003).…”
Section: Introductionmentioning
confidence: 99%